Mathematical reasoning writing and proof - Sundstrom, Theodore A. (Upper Saddle River, N.J. Prentice Hall, 2003)
Designed as a text for a first course in the college mathematics curriculum that focuses on the formal development of mathematics, this book explains how to read and understand mathematical definitions and proofs, and how to construct and write mathematical proofs. Emphasis is on writing mathematical exposition, with guidelines for writing proofs incorporated throughout the text. Learning features include preview activities that prepare students to participate in classroom discussion and activities for in-class group work. Coverage encompasses logical reasoning, constructing and writing proofs, set theoy, mathematical induction, functions, and topics in number theory and set theory
Introduction to writing in mathematics -- Logical reasoning -- Constructing and writing proofs in mathematics -- Set theory -- Mathematical induction -- Functions -- Equivalence relations -- Topics in number theory -- Topics in set theory
Includes index.
Keywords: Proof theory